1994
DOI: 10.1073/pnas.91.21.9730
|View full text |Cite
|
Sign up to set email alerts
|

The Ada protein acts as both a positive and a negative modulator of Escherichia coli's response to methylating agents.

Abstract: The adaptive response of Escherichia coli protects the cells against the toxic and mutagenic effects of ceilain alkylating agents. The major effector molecule regulating this response is the 39-kDa Ada protein, which functions as both a DNA repair protein and a transcriptional activator. Ada removes methyl groups from phosphotriester and 0P-methyluanine lesions in DNA, irreversibly transferring them to cystehie residues at positions 69 and 321, respectively. When methylated at Cys-69, Ada is converted into a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 35 publications
1
37
0
1
Order By: Relevance
“…We have previously demonstrated that physiologically relevant concentrations of unmethylated Ada protein are able to inhibit methylated Ada-promoted ada transcription both in vitro and in vivo (18). This ada-specific inhibition does not occur at the alkA promoter either in vitro or in vivo.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…We have previously demonstrated that physiologically relevant concentrations of unmethylated Ada protein are able to inhibit methylated Ada-promoted ada transcription both in vitro and in vivo (18). This ada-specific inhibition does not occur at the alkA promoter either in vitro or in vivo.…”
Section: Discussionmentioning
confidence: 96%
“…␤-Galactosidase assays were performed as described elsewhere (18). Cells were grown in M9 minimal medium (12) to an optical density (OD) of 0.2 to 0.3.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations